Personal assistance for children and adolescents (0-18) with physical impairments. - Montgomery, P; Mayo-Wilson, E; Dennis, J (2008)
BACKGROUND: There is a high and increasing prevalence of impairments among children and adolescents in the West. Many countries offer personal assistance in the form of individualised support for people living in the community by a paid assistant other than a healthcare professional for at least 20 hours per week. OBJECTIVES: To assess the effectiveness of personal assistance for children and adolescents with physical impairments, and the impacts of personal assistance on others, compared to other interventions. SEARCH STRATEGY: Electronic databases including CENTRAL, MEDLINE, EMBASE, CINAHL, PsycINFO, ERIC, Dissertation Abstracts International and a variety of specialist Swedish databases were searched from 1980 to June 2005; reference lists were checked; 345 experts, organisations, government bodies and charities were contacted in an attempt to locate relevant research. SELECTION CRITERIA: Children and adolescents with physical impairments (0-18 years) living in the community who require assistance to perform tasks of daily living (e.g., bathing and eating) and participate in normal activities due to permanent impairments. Controlled studies of personal assistance in which participants were prospectively assigned to study groups and in which control group outcomes were measured concurrently with intervention group outcomes were included. DATA COLLECTION AND ANALYSIS: Titles and abstracts were examined by two reviewers. 130 full papers were examined. None met the inclusion criteria. MAIN RESULTS: No eligible studies were found. AUTHORS' CONCLUSIONS: Research in this field is limited. When implementing new programmes, recipients could be randomly assigned to different forms of assistance. While advocates may support personal assistance for myriad reasons, this review demonstrates that further studies are required to determine which models of personal assistance are most effective and efficient for particular people.